The relationship between market competition and capital structure in Malaysia/ Siti Norafizah Husin - Husin, Siti Norafizah (2017)
The study of this paper aims to determine the relationship of capital structure consists of debt ratio and market competition in Malaysia based on 35 listed companied in Bursa Malaysia. The listed company in Bursa Malaysia that has been chosen in this study from construction, properties and industrial products sector for four year period of 2012 to 2015. The Pooled Ordinary Least Square (OLS) method has been use in measuring the relationship in panel data. The data of listed company in Malaysia has been collected from e-sources in DataStream and database online that provided in library UITM. All the data collected refer to the performance of company that stated from the annual report which is financial ratio. The variables return on asset has impact toward debt ratio due to larger asset in the firm can affect the level of leverage. For size of firm also would affect the debt ratio because of the larger firm will has a lower debt and better firm performance. When firm has higher growth rate it shown that the firm has better financial because of higher income and more flexibility. The finding in this study has been obtained which is variables return on asset has negative relationship to the dependent variable while size of firm and growth rate has positive relationship toward debt ratio.